Az újonnan iparosodó délkelet-ázsiai országok világgazdasági szerepkörének alakulása 1970–1993 között - Szegedi, Gabriella (Tér és Társadalom, 1996)
A 1991 study of the Roman Club emphasised, as a "geo-strategic change", the appearance and development of three industrial and trading groups, blocks, namely the North American block, the EC countries and Japan with the NIE + ASEAN countries. They placed a special emphasis on the fact that the countries which reacted in the most flexible and effective way to the fast changes in technology in the past twenty years were Japan and the NIE-NIC, also the ASEAN countries. In our study, the south-east Asian region covers eight newly industrialised countries, namely Hongkong, South Korea, Singapore, Taiwan, the Philippines, Indonesia, Malaysia and Thailand. The purpose of this study is to analyse the evolution of the role of these countries in the world economy and the growth in their importance in world trade, trying to find tendencies, general features and visible differences in the period 1970-1993.